2017
DOI: 10.1371/journal.pone.0175229
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of weather and air pollution on atopic dermatitis symptoms in children: A panel study in Korea

Abstract: IntroductionThe effects of weather and air pollution on the severity and persistence of atopic dermatitis (AD) are important issues that have not been investigated in detail. The objective of our study was to determine the short-term effects of meteorological variables and air pollution on AD symptoms in children.MethodsWe enrolled 177 AD patients with 5 years or younger from the Seoul Metropolitan Area, Korea, and followed for 17 months between August 2013 and December 2014. Symptoms records of 35,158 person-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 48 publications
6
85
3
4
Order By: Relevance
“…Air pollutants were found to have harmful effects on AD in our study, which was consistent with previous studies . We compared our results with a very similar study done in Chengdu, south‐western China .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Air pollutants were found to have harmful effects on AD in our study, which was consistent with previous studies . We compared our results with a very similar study done in Chengdu, south‐western China .…”
Section: Discussionsupporting
confidence: 92%
“…A similar study in Shanghai, China also found the strongest effects between air pollutants and outpatient visits for eczema at lag0 . A panel study in Korea found an increase in PM 10 and NO 2 by 10 units increased the risk of eczema symptoms on the same day by 3.2% (95% CI: 1.5%, 4.9%) and 5.0% (95% CI: 1.4%, 8.8%), respectively . Our results, combined with the above previous studies, suggested that AD symptoms worsen and then people go to a clinic immediately.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The model was adjusted for confounding factors, such as age, sex, season, SCORAD at the initial visit, and fever. Result of this analysis was presented in our previous report …”
Section: Methodsmentioning
confidence: 99%
“…Air pollutants are risk factors of allergic diseases, such as asthma and atopic dermatitis (AD) . In our previous studies, we elucidated that several indoor and outdoor air pollutants, such as particulate matter of <10 μm diameter (PM 10 ) and total volatile organic compounds, were associated with worsening of AD symptoms. These air pollutants appear to induce barrier dysfunction and/or immune dysregulation in the skin; which might be mediated by oxidative stress .…”
Section: Introductionmentioning
confidence: 99%